Effect of Cultivar Resistance and Soil Management on Spatial–Temporal Development of Verticillium Wilt of Olive: A Long-Term Study - Ostos, Eduardo; Garcia-Lopez, María Teresa; Porras, Rafael; Lopez-Escudero, Francisco J.; Trapero-Casas, Antonio; Michailides, Themis J.; Moral, Juan (Frontiers in Plant Science, 2020)
Verticillium wilt, caused by Verticillium dahliae, challenges olive cultivation and an Integrated Disease Management (IDM) approach is the best-suited tool to combat it. Since 1998, an IDM strategy in an orchard (called Granon, Spain) of the susceptible cv. Picual was conducted by increasing planting density with moderately resistant cv. Frantoio, chemical weed control, and replanting of dead olives with cv. Frantoio following soil solarization. The Verticillium wilt epidemic in Granon orchard was compared to the epidemic in a non-IDM orchard (called Ancla, Spain) with plowed soil and dead Picual olives replanted with the same cultivar. Field evaluations (2012–2013) showed an incidence and severity of the disease as Picual–Ancla > Picual–Granon > Frantoio–Granon. The spatiotemporal dynamics of the Verticillium epidemics from 1998 to 2010 were monitored with digital images using SIG. The annual tree mortalities were 5.6% for Picual olives in Ancla orchard, and 3.1 and 0.7% for Picual and Frantoio olives in Granon orchard, respectively. There was a negative relationship between the mortality of olive trees (%) by the pathogen and the height (m) above sea level. The annual mortality of cv. Picual olives was positively correlated with spring rainfalls. The Index of Dispersion and beta-binomial distribution showed aggregation of Verticillium-dead olives. In conclusion, this IDM strategy considerably reduced the disease in comparison with traditional agronomic practices.